What we talk about when we talk about interactivity: Empowerment in public discourse. (July 2017) - Barry, Marguerite; Doherty, Gavin
This study offers new insights into interactivity by examining its association with empowerment in public discourse. Using data from 20 years of newspaper coverage, a mixed methods analysis reveals different 'modes' of interactivity in discourse. Empowerment is the dominant mode of interactivity despite substantial changes in technologies and uses over this time. A content analysis shows that older discourses associate interactivity with specific technologies, while recent discourses use more universal terms. The discourse analysis illustrates the range of empowerment found in different interactive experiences, from basic data access to collaboration across communities, even reaching beyond communication events. The study offers a new model for understanding interactivity and empowerment based on the potential in communications for action, context, strategies and outcomes . This layered and flexible approach has appeal for digital media research and production.